Analysis of Psychosocial Consequences of Covid-19 Disease and Vaccination in the Elderly: A Qualitative Study - Sepehrtaj, Arefeh; Darvishi, Nesa; Javadi, Seyyed Mohammad Hossein; Bahonar, Fahimeh; Younesi, Seyed Jalal (Advances in Nursing & Midwifery, 2022)
Introduction: The elderly are one of the sensitive groups at risk of developing Covid-19 disease. We aimed to investigate the psychosocial consequences of Covid-19 disease and vaccination in the elderly. Methods: The phenomenological method was used in the current study. The study population included all the elderly receiving the Covid-19 vaccine in Sari city, Iran. 13 individuals were selected through purposeful sampling method who were interviewed afterwards. The Colaizzi Phenomenological method was used to analyze the data. Results: Data analysis led to the identification of 5 main themes, 11 sub-themes, and 56 primary open themes. The first major theme was "psychological status." Psychological status included a set of reactions that included the following sub-themes: 1-Positive psychological status, 2-Negative psychological status. The second main theme was "recreational and communication status". Recreational and communication status was a set of behaviors that included the following sub-themes: 1-Health-based personal entertainment and communication, 2-Destructive entertainment and communication. The third main theme was physical and health status with these central themes: 1-Psychological and behavioral consequences of receiving the vaccine, 2-Physical complications of receiving the vaccine, and 3-Change in physical examinations. The economic status as the fourth main theme included: 1-High cost of Covid-19, 2-Career problems. Finally, the last major theme was lifestyle with the following central codes: 1-Pre-corona family plans and, 2-Post-corona family plans. Conclusions: The results showed that it is important to pay attention to the experience of the elderly in the coronavirus crisis and that the devastating consequences of Covid-19 can be avoided.